2010
DOI: 10.1098/rspb.2010.0234
|View full text |Cite
|
Sign up to set email alerts
|

To eat or not to eat: egg-based assessment of paternity triggers fine-tuned decisions about filial cannibalism

Abstract: Filial cannibalism occurs in many animal species ranging from insects to mammals, and is especially well described in teleost fishes. Numerous causes may lead to this behaviour, e.g. certainty of paternity. However, the cues males use to assess their paternity often remain unknown. One possible way to differentiate between own and foreign offspring is by using egg cues. Nevertheless, in egg-laying species, evidence for this is still scarce. In this study, male three-spined sticklebacks (Gasterosteus aculeatus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 66 publications
0
37
1
Order By: Relevance
“…This is in contrast with, for example, three-spined sticklebacks, Gasterosteus aculeatus , where smaller males were more reluctant to attack intruders [33]. However, other studies have found, like us, that smaller males can be more aggressive.…”
Section: Discussioncontrasting
confidence: 96%
“…This is in contrast with, for example, three-spined sticklebacks, Gasterosteus aculeatus , where smaller males were more reluctant to attack intruders [33]. However, other studies have found, like us, that smaller males can be more aggressive.…”
Section: Discussioncontrasting
confidence: 96%
“…Kin recognition, the capacity for distinguishing kin from non-kin using genetic similarity or any cue that is correlated with kinship (HOLMES 2004), has been evidenced in several animal species, both vertebrate (SHARP et al 2005;KRUCZEK 2007;MOORE 2007;SHERBORNE et al 2007;GREEN et al 2008;MEHLIS et al 2010) and invertebrate (LIZÉ et al 2006;PATTERSON et al 2008;SCHNEIDER & BILDE 2008;DE NARDIN & ARAÚJO 2011), in plants (DUDLEY & FILE 2007) and also in mycetozoa (MEHDIABADI et al 2006(MEHDIABADI et al , 2009OSTROWSKI et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…From the female's point of view, it is therefore best to choose a male that provides care without cannibalizing any, or as few as possible, of her eggs. Although other factors, such as mate availability, paternity and nutritional status may also influence whether eggguarding males show filial cannibalism (e.g., Mehlis et al 2009Mehlis et al , 2010Myint et al 2011), our main focus here is on the effects of brood size.…”
Section: Introductionmentioning
confidence: 99%